2009
DOI: 10.1007/s11071-009-9493-0
|View full text |Cite
|
Sign up to set email alerts
|

Frequency domain analysis of a dimensionless cubic nonlinear damping system subject to harmonic input

Abstract: Monograph:Jing, X.J. and Lang, Z.Q. (2008) Frequency domain analysis of a dimensionless cubic nonlinear damping system subject to harmonic input. Research Report. ACSE Research Report no. 971 . Automatic Control and Systems Engineering, University of Sheffield eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…However, nonlinear damping is known to be significant at least in some cases. For example, the effect of nonlinear damping for the case of strictly dissipative force, being proportional to the velocity to the nth power, on the response and bifurcations of driven Duffing [55][56][57][58] and other types of nonlinear oscillators [45,57,[59][60][61] has been studied extensively. Also, nonlinear damping plays an important role in parametrically excited mechanical resonators [42,62] where without it, solutions will grow without bound [45,63].…”
Section: Introductionmentioning
confidence: 99%
“…However, nonlinear damping is known to be significant at least in some cases. For example, the effect of nonlinear damping for the case of strictly dissipative force, being proportional to the velocity to the nth power, on the response and bifurcations of driven Duffing [55][56][57][58] and other types of nonlinear oscillators [45,57,[59][60][61] has been studied extensively. Also, nonlinear damping plays an important role in parametrically excited mechanical resonators [42,62] where without it, solutions will grow without bound [45,63].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies [1] showed that the implementation of nonlinear damping may bring improvements to the isolation performance of a lightly linear damped isolator by suppressing its resonance amplitude without degrading its high-frequency isolation efficiency. Recent rigorous theoretical works [2][3][4][5] also pointed out that the cubic nonlinear damping (denoted as the first type of nonlinear damping in this paper), i.e., f I d ∝ṙ 3 ( f I d is the damping force andṙ denotes the relative velocity), can suppress the resonance amplitude while keep the force transmissibility almost unchanged at low or high frequencies for a singledegree-of-freedom (SDOF) isolator. This concept was also extended to the study of multi-degree-of-freedom (MDOF) isolation problems by Peng [6] and Lang [7].…”
Section: Introductionmentioning
confidence: 88%
“…As been discussed above, in order to simultaneously meet the requirements of low resonance amplitude and good isolation performance at high-frequency range, these scholars [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] studied the lightly damped or even no damped linear isolators (already have good isolation efficiency at high frequencies) and added nonlinear damping elements to improve their poor resonance performances. While in this paper, we develop another novel way by presenting a sufficient damped isolator (naturally owns low resonance amplitude) and employ a nonlinear spring to reduce its vibration transmissibility at high frequencies without deteriorating its resonance performance.…”
Section: Introductionmentioning
confidence: 99%
“…Should speed be multiplied by n times, the dissipated power would increase n 2 times. In addition, non-linear effects are usually present in the system [15].…”
Section: Magnetic Dampersmentioning
confidence: 99%